RENCANA PEMBANGUNAN JANGKA PANJANG (RPJP), SUSTAINABLE DEVELOPMENT GOALS (SDGS) AND MAQASID AL-SHARIAH: THE CASE OF KABUPATEN REMBANG - Abdul Qoyum; prasojo prasojo (Universitas Darussalam Gontor, 2020)
The objective of this paper is to analyze Rencana Jangka Panjang Daerah Kabupaten Rembang from SDGs and Maqosid Shariah point of view. This paper find that, SDGs only confirm with 4 element maqosid syariah, except the first maqosid. For the secular countries, it is not create any problems, but for the Regency like Rembang, the fulfilment of first maqosid namely “safeguarding religion” is very important. Hence, adobting SDGs need to be modified. In majority SDGs are connects with the 4th and 5th objective of shariah. It means that, from Maqosid Syariah view, SDGs are very focus on the economic and long-life aspect. While, there is no goal of SDGs that has intended to the development of religion. If compared to RPJPD, for the first objective of Shariah there is no specific indication that Rembang has concern on this. For the second objective of Shariah, it has strong relationship with SDGs, thus, in RPJPD there are some real concern from the government in achieving this goal. Indeed, for the goal related to progency and economic aspect, RPJPD of Rembang are very much focus on the fulfilment of this. Hence, there are many program related to this goal. Contrastly, although, education that confirm to SDGs and also 3rd Maqosid syariah, has been accommodated in RPJPD, but this program is away from the main characteristics of Rembang, namely Pesantren and Madrasah. In RPJPD, it is clearly indicated that, the final goal of education is just in term of achieving scores such as APS and APM, rather than character building which has been done by Pesantren and Madrasah. Keyword: RPJP, SDGs, Maqoshid Syari’ah